2008
DOI: 10.1093/ajcn/88.4.906
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of adaptive thermogenesis in subjects who have maintained a reduced body weight

Abstract: Background: After weight loss, total energy expenditure-in particular, energy expenditure at low levels of physical activity-is lower than predicted by actual changes in body weight and composition. An important clinical issue is whether this reduction, which predisposes to weight regain, persists over time. Objective: We aimed to determine whether this disproportionate reduction in energy expenditure persists in persons who have maintained a body-weight reduction of ͧ10% for 1 y. Design: Seven trios of sex-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
285
2
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(303 citation statements)
references
References 41 publications
(42 reference statements)
7
285
2
9
Order By: Relevance
“…Weight loss is a physiologically and biochemically heterogeneous process, and decreases in energy expenditure with weight loss have been shown to vary from -38% to -6% in a controlled experiment where subjects lost 10% of their weight 24,25 . Strong hormonal influences drive weight regain after weight loss 26 , and the individual variation in this process has yet to be characterised.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss is a physiologically and biochemically heterogeneous process, and decreases in energy expenditure with weight loss have been shown to vary from -38% to -6% in a controlled experiment where subjects lost 10% of their weight 24,25 . Strong hormonal influences drive weight regain after weight loss 26 , and the individual variation in this process has yet to be characterised.…”
Section: Discussionmentioning
confidence: 99%
“…Energy restriction induces a reduction in REE below predicted values, as based on the new body composition reached after underfeeding-induced weight loss. [16][17][18][19] The REE reduction in obese subjects losing 10-20% of initial weight, adjusted for changes in body composition, ranges between 3 and 6% of the initial TEE value. Van Gemert et al 20 observed in morbid obese subjects losing on average one-third of initial weight, an average reduction of 7% at 1 year after the start of weight loss and of 4% when weight loss was maintained for more than 3 years.…”
Section: Changes In Food Intake and Energy Expenditurementioning
confidence: 99%
“…The adaptive AEE reduction induced by restricting energy intake in overweight and obese subjects is larger, and can be explained by a reduction in body movement and an increase in muscle efficiency. 17,21 However, Camps et al 21 observed an energy restriction-induced adaptive reduction of AEE that is not sustained when energy intake meets again TEE. 21 The energy restriction-induced adaptive reduction of REE persists perhaps indefinitely.…”
Section: Changes In Food Intake and Energy Expenditurementioning
confidence: 99%
See 1 more Smart Citation
“…The simple prescriptions to "eat less and move more" are becoming complicated by research findings that show how a 5 wide range of metabolic processes are affected by weight loss and implicated in the weight regain that often follows (e.g., Rosenbaum, Hirsch, Gallagher, & Leibel, 2008;Sumithran et al, 2011). Despite the increasing sophistication of exercise and nutrition programs designed for weight loss, sustained weight loss remains an elusive goals for many people; although the precise success rate for long term maintenance of weight loss is difficult to determine, a recent review suggests that only around 17% of Americans who have ever been overweight or obese have maintained a loss of at least 10% of their body weight for at least one year (Kraschnewski et al, 2010).…”
Section: Weight Loss Is a Fraught Goalmentioning
confidence: 99%